Effects of bystander programs on the prevention of sexual assault among adolescents and college students: a systematic review - Kettrey, Heather Hensman (Campbell Systematic Reviews, 2019)
Sexual assault is a significant problem among adolescents and college students across the world. One promising strategy for preventing these assaults is the implementation of bystander sexual assault prevention programs, which encourage young people to intervene when witnessing incidents or warning signs of sexual assault. This review examines the effects bystander programs have on knowledge and attitudes concerning sexual assault and bystander behavior, bystander intervention when witnessing sexual assault or its warning signs, and participants’ rates of perpetration of sexual assault.